2018
DOI: 10.1088/1755-1315/125/1/012138
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test pepsinogen I and combination with tumor marker CEA in gastric cancer

Abstract: Gastric cancer (GC) is the fifth leading cause of cancer and the third leading cause of cancer-related mortality globally. Human pepsinogens (HP) are considered promising serological biomarkers for the screening of atrophic gastritis (AG) and GC. HP are biochemically and immunochemically classified into two groups: pepsinogen I (PG I) and PG II. Carcinoembryonic antigen (CEA) is a glycoprotein, which is present in normal mucosal cells but increased amounts are associated with adenocarcinoma, especially colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Actually, the combination of serum PG and other indicators is successfully used for the prediction of GC [29]. Sembiring J et al have shown that PGI combined with CEA can be used for the diagnosis of GC from non-GC individuals with a sensitivity of 94.1% and a specificity of 80% [30]. Niu WW et al have indicated that the sensitivity and specificity of miR-92a combined with PG on GC is 86.49 and 89.32%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the combination of serum PG and other indicators is successfully used for the prediction of GC [29]. Sembiring J et al have shown that PGI combined with CEA can be used for the diagnosis of GC from non-GC individuals with a sensitivity of 94.1% and a specificity of 80% [30]. Niu WW et al have indicated that the sensitivity and specificity of miR-92a combined with PG on GC is 86.49 and 89.32%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sembiring J et al have shown that PGI combined with CEA can be used for the diagnosis of GC from non-GC individuals with a sensitivity of 94.1% and a specificity of 80% 30 . Niu WW et al have indicated that the sensitivity and specificity of miR-92a combined with PG on GC is 86.49% and 89.32%, respectively 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the combining of serum PG and other indicators is successfully used for the prediction of GC development 32 . A recent diagnostic test PGI and combination with tumor marker CEA in 32 patients suspected with GC shows that PGI + CEA can be used for diagnosis of GC from non-GC individual with sensitivity of 94.1% and specificity of 80% 33 . Niu et al indicates that there was a high diagnostic value of miR-92a combined with PG in GC development 34 .…”
Section: Discussionmentioning
confidence: 99%